Design and Evaluation of a Concentrated Solar-Powered Thermal-Pasteurization System (Journal of Solar Energy Research Updates, 2019)
A device has been designed, constructed, and tested for heating fluids using solar energy. The device heats water to levels to kill pathogens by a parabolic reflecting surface that concentrates solar energy along an axis. Among the components that increase the thermal performance of the system is a thermally actuated valve, which controls the temperature and the thermal exposure duration of the fluid to cause deactivation of targeted pathogens. Also, a novel fluid-to-fluid heat exchanger arranged in counter flow is used.Experiments were performed with a water solution containing non-pathogenic Escherichia coli K-12 MG1655 (E. coli) bacteria. The results showed that the system is capable of pasteurization to levels where no living pathogens were detected in the heated fluid. The experiments were carried out over a wide range of temperatures and exposure durations to test the device and the underlying mathematical model. E. coli log reductions greater than 1 were achieved in all cases and it is shown that arbitrary values of reduction can be achieved with appropriate temperature/time settings.